Product innovation for the ecological transition. Brick and glass recycling - Adolfo F. L. Baratta; Jacopo Andreotti; Luca Trulli; Laura Calcagnini (Agathón, 2023)
In the thematic environment of conscious use and material resource recycling, the Department of Architecture of the Roma Tre University is currently conducting a research line focused on environmental product innovation. This line consists of two application studies involving manufacturing companies in the construction sector. Both types of research address the issue of additives in the mix design of bricks and concrete, respectively, to achieve better-performing products. The results led to the prototyping of two products: a brick, made from waste replacing a fraction of clay with a mixture of bentonite sludge and metal residues, and a concrete screed mix, made from construction and demolition glass waste replacing natural aggregates.